The Effect of Size on the Splitting Strength of Cubic Concrete Members - Ince, R.; Gor, M.; Eren, M. E.; Alyamac, K. E. (Wiley, 2015)
In the study of concrete fractures, split-tension specimens, such as cylinders, cubes and diagonal cubes, are frequently preferred to beams. However, experimental investigations on concrete reveal that for the same specimen geometry, the nominal strength of specimen decreases with increasing specimen size. This phenomenon is named as the size effect in the fracture mechanics of concrete. Although nominal strength is also highly affected by the width of the distributed load in the split-tension cylinder and cube specimens, this effect can be negligible within the practical range of the load-distributed width in the diagonal cubes. However, the number of theoretical and experimental studies with diagonal split-tension specimens is limited. Besides, a size effect formula for estimating the split-tensile strength of the diagonal cube specimens has not been proposed. In this study, nine series of cube and diagonal cube specimens, with three different sizes but similar geometries, were tested under different load-distributed widths. The ultimate loads obtained from the test results are analysed by the modified size effect law. Subsequently, prediction formulas are proposed, and they are compared with historical test data from the split-cylinder specimens.
Keywords: concrete; modified size effect law; splitting strength